x - [ 17/2 - ( -3/7 + 5/3 ) ] = -1/3
GIÚP VỚI
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Giải:
a) \(2\dfrac{17}{20}-1\dfrac{15}{11}+6\dfrac{9}{20}:3\)
\(=\dfrac{57}{20}-\dfrac{26}{11}+\dfrac{129}{20}:3\)
\(=\dfrac{107}{220}+\dfrac{43}{20}\)
\(=\dfrac{29}{11}\)
b) \(4\dfrac{3}{7}:\left(\dfrac{7}{5}.4\dfrac{3}{7}\right)\)
\(=\dfrac{31}{7}:\left(\dfrac{7}{5}.\dfrac{31}{7}\right)\)
\(=\dfrac{31}{7}:\dfrac{31}{5}\)
\(=\dfrac{5}{7}\)
c) \(\left(3\dfrac{2}{9}.\dfrac{15}{23}.1\dfrac{7}{29}\right):\dfrac{5}{23}\)
\(=\left(\dfrac{29}{9}.\dfrac{15}{23}.\dfrac{36}{29}\right):\dfrac{5}{23}\)
\(=\dfrac{60}{23}:\dfrac{5}{23}\)
\(=12\)
A = ( -4/5 + 4/3 ) + (-5/4 + 14/5) - 7/3
= 8/15 + 31/20 - 7/3
= 25/12 - 7/3
= -1/4
B = 8/3 x 2/5 x 3/8 x 10x 19/92
= 16/15 x 15/4 x 19/92
= 4x19/92
= 19/23
C = - \(\dfrac{5}{7}\) x \(\dfrac{2}{11}\) + \(\dfrac{-5}{7}\) x \(\dfrac{9}{14}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{10}{77}\) - \(\dfrac{45}{98}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{635}{1078}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{36195}{61446}\) + \(\dfrac{1078}{61446}\)
= - \(\dfrac{35117}{61446}\)
\(-\frac{1}{10}< =x< =\frac{3}{5}\)
\(\frac{-4}{9}< x< =\frac{2}{3}\)
Tính :
1-2+3-4+5-6+...+201-202
=(1-2)+(3-4)+(5-6)+...+(201-202) (có 101 cặp)
=(-1)+(-1)+(-1)+...+(-1)
=(-1).101=-101.
Tìm x là số nguyên :
30-(x+1)=-17
x+1=30-(-17)
x+1=47
x=47-1
x=46
Vậy x=46.
x(|15|-10)=53
x(15-10)=53
x.5=53
x=53:5
x=52=25
Vậy x=25
2x+5=7-x-5
2x+x+5=7-5
3x+5=2
3x=2-5
3x=-3
x=(-3):3
x=-1
Vậy x=-1.
\(\frac{17}{33}.\frac{2}{5}+\frac{3}{5}.\frac{17}{33}-\frac{17}{33}\)
\(=\frac{17}{33}\times\frac{2}{5}+\frac{3}{5}\times\frac{17}{33}-\frac{17}{33}\times1\)
\(=\frac{17}{33}\times\left(\frac{2}{5}+\frac{3}{5}-1\right)\)
\(=\frac{17}{33}\times\left(1-1\right)\)
\(=\frac{17}{33}\times0=\frac{17}{33}\)
x - [ 17/2 - (-3/7 + 5/3) ] = -1/3
x - [ 17/2 + 3/7 - 5/3 ] = -1/3
x - 305/42 = -1/3
x = -1/3 + 305/42
x = 97/14
HT !
\(x-\left[\frac{17}{2}-\left(-\frac{3}{7}+\frac{5}{3}\right)\right]=-\frac{1}{3}\)
\(x-\left[\frac{17}{2}-\frac{26}{21}\right]=-\frac{1}{3}\)
\(x-\frac{305}{42}=-\frac{1}{3}\)
\(x=-\frac{1}{3}+\frac{305}{42}\)
\(x=\frac{97}{14}\)